946 Reducing the use of seclusion: creating a culture of safety and teamwork in a new inpatient psychiatric unit. (21st November 2017) - Powell, Nicole; Valleru, Jahnavi; Krishna, Rajeev; Finney, Jodi
Abstract : Background: Seclusion is an intensive intervention employed in inpatient mental health units to guarantee safety when de-escalation methods have been exhausted. High rate of seclusion are associated with higher employee injury rate, lower staff engagement and increased patient length of stay. Objectives: Our aim is to reduce seclusion rates in all admitted patients in inpatient psychiatry from a baseline of 136 to less than 110 per 1000 patient days by December 2016 and sustain for 12 months. Methods: A multidisciplinary team developed an Aim and Key Driver Diagram focused on reducing seclusions. Evidence based interventions included milieu management techniques, proactive patient engagement and staff training on trauma informed approaches, physical deflection, and reinforcement principles. Other successful Plan-Do-Study-Act's (PDSA's) include small patient groups and skill-appropriate programming to reduce opportunities for escalating behaviours and increase patient success. Results: By 1st quarter 2017, seclusion rates were reduced from 136 to 60 seclusions per 1000 patient days (56% reduction) and sustained for 12 months. In addition to seclusion rates, we achieved a 40% reduction in duration of seclusions, a 55% reduction in mechanical restraints and a 72% reduction in employee injuries. Conclusions: Seclusion in children and adolescent mental health units can be significantly reduced through systematic application of quality improvement methodology to revise unit programming and address training and awareness issues. We implemented several effective and less-disruptive interventions while we established a new unit and trained inexperienced staff. These strategies may help impact care of patients in other child and adolescent mental health units.